STRATEGI PERBAIKAN - PENGGANTIAN BERDASARKAN UMUR PRODUK UNTUK GARANSI SATU DIMENSI - Dyah Ika Rinawati (TEKNIK, 2011)
When the manufacturer selling products with warranties, it causes additional costs (called warranty costs) toservice any claims under warranty. Reducing warranty costs is an issue of great interest to manufactures. Thethree ways to reduce warranty costs i.e. improving product reliability, use of preventive maintenance andwarranty servicing strategy.This research deals with a warranty servicing strategy for items sold with a one dimensional warranty where theperiod offered is relatively long. For instance, a computer warranted for three years. For repairable productssold with free repairable warranty (FRW), the manufacturer has the option of either repairing or replacing thefailed item with a new one.In the strategy studied, the decision of repairing or replacing the failed item under warranty is based on its ageat failure. Under the strategy, for failures with age being greater than or equal to threshold parameter will berectified by replacement and all other failures under warranty will be repaired. This strategy is characterized bya threshold parameter which minimizes the expected warranty cost. The optimal parameter is sought by usingnumerical computation. Some numerical examples are given for the purposes of illustration.